Concept of Persuasive Education Based on Andragogical Approaches in Al-Qur'an (Study of Hiwar Prophet Khidir Educate Prophet Musa Surah Al-Kahfi 60-82) - Abdul Kirom (Maharot : Journal of Islamic Education, 2022)
This research aims 1) to reveal the concept of persuasive education with an andragogical approach in the hiwar educes prophet Khidir to the prophet Musa in the QS. Al-Kahfi 60-822) to reveal the values of persuasive education based on the andragogy approach in the hiwar of the prophet Khidir in the prophet Musa QS. Al-Kahfi 60-82. Researchers use a qualitative approach with the type of library research. The secondary data source in this research is the Al-Qur'an and the second is the interpretation of Al-Misbah. To analyze using content analysis. The results of this research show that 1) concept of persuasive education with an andragogical approach in education of the Prophet Khidir to the Prophet Musa in QS. Al-Kahf 60-82 include: a) concept of idealistic reality of science, b) concept of stimulus response, c) concept of self, d) concept of experience, e) concept of readiness to learn, f) learning orientation. 2) values of persuasive education based on the andragogy approach in hiwar prophet Khidir on prophet Musa QS. Al-Kahfi 60-82, namely a) humility (tawadhu'), b) value of seriousness and sincerity in seeking knowledge, c) value of benefits for others, d) value of patience and tolerance, e) value of honesty, f) value of gentleness, g) value of discipline, and h) value of courage.